Puumala Hantavirus-Induced Hemorrhagic Fever with Renal Syndrome Must Be Considered across the Borders of Nephrology to Avoid Unnecessary Diagnostic Procedures. - Daniel Kitterer; Stephan Segerer; M Dominik Alscher; Niko Braun; Joerg Latus (PLoS ONE, 2015)
Nephropathia epidemica (NE), a milder form of hemorrhagic fever with renal syndrome, is caused by Puumala virus and is characterized by acute kidney injury and thrombocytopenia.A cross-sectional prospective survey of 456 adult patients with serologically confirmed NE was performed.Of the 456 investigated patients, 335 had received inpatient treatment. At time of admission to hospital, 72% of the patients had still an AKI and thrombocytopenia was present in 64% of the patients. The 335 patients were treated in 29 different hospitals and 6 of which had nephrology departments. 10 out of 335 patients received treatment in university hospitals and 63% of patients admitted themselves to hospital. Initially, the patients were admitted to 12 different clinical departments (29% of the patients were referred to a nephrology department) and during the course of the disease, 8% of the patients were transferred to another department in the same hospital and 3% were transferred to a nephrology department at another hospital. Regarding diagnostic procedures, in 28% of the inpatients computed tomography to exclude pulmonary embolism or due to severe gastrointestinal symptoms, lumbar puncture to exclude meningitis, magnetic resonance tomography of the brain owing to suspected stroke because of visual disorders, gastroscopy, or colonoscopy due to gastrointestinal symptoms was performed at time of admission to hospital.NE must be considered by physicians across the borders of nephrology to avoid unnecessary diagnostic procedures especially in areas where NE is endemic.